Evaluation of (18)F-FDG PET/CT Parameters for Detection of Lymph Node Metastasis in Cutaneous Melanoma - Cha, Jongtae (Nucl Med Mol Imaging, 2017)
PURPOSE: The purpose of this study was to investigate the value of (18)F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) parameters in the detection of regional lymph node (LN) metastasis in patients with cutaneous melanoma. METHODS: We evaluated patients with cutaneous melanoma who underwent FDG PET/CT for initial staging or recurrence evaluation. A total of 103 patients were enrolled, and 165 LNs were evaluated. LNs that were confirmed pathologically or by follow-up imaging were included in this study. PET parameters, including maximum standardized uptake value (SUVmax), total lesion glycolysis and tumour-to-liver ratio, were used to determine the presence of metastases, and the results were compared with CT-determined LN metastasis. Receiver operating characteristic (ROC) curve analysis was used to determine the optimal cut-off values of the FDG PET parameters. RESULTS: A total of 93 LNs were malignant, and 84 LNs were smaller than 10 mm. In all 165 LNs, an SUVmax of >2.51 showed a sensitivity of 73.1%, a specificity of 88.9%, and an accuracy of 80.0% in detecting metastatic LNs. CT showed a higher specificity (87.3%) and lower accuracy (65.5%). For non-enlarged regional LNs (<10 mm), an SUVmax cut-off value of 1.4 showed the highest negative predictive value (81.3%). For enlarged LNs (≥10 mm), an SUVmax cut-off value of 2.4 showed the highest sensitivity (90.7%) and accuracy (88.9%) in detecting metastatic LNs. CONCLUSIONS: In patients with cutaneous melanoma, an SUVmax of >2.4 showed a high sensitivity (91%) and accuracy (89%) in detecting metastasis in LNs ≥1 cm, and LNs <1 cm with an SUVmax <1.4 were likely to be benign.